Using Using Discussion Activities to Increase Motivation and Speaking Proficiency of Second-Year EFL Students at Hanoi University of Business and Technology: An Action Research Study - Lã, Thị Hường (University of Languages and International Studies, 2017)
The study was carried out with an attempt to increase motivation and speaking proficiency of the second-year EFL students at Hanoi University of Business and Technology by using discussion activities. The subjects participating in the research were 14 seco (...)